2016
DOI: 10.1016/j.ijrobp.2016.06.1632
|View full text |Cite
|
Sign up to set email alerts
|

Staged Reconstruction Brachytherapy Has Lower Overall Cost in Recurrent Soft Tissue Sarcoma

Abstract: Purpose: Adjuvant brachytherapy (AB) with immediate (IR) and staged reconstruction (SR) are distinct treatment modalities available for patients with recurrent soft tissue sarcoma (STS). Although SR may offer local control and toxicity benefit, it requires additional upfront procedures, and there is no evidence that it improves overall survival. With the importance of value-based care, our goal is to identify which technique is more cost effective.Material and methods: A retrospective review of 22 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…24 Another study from 2016 considered recurrent STS in the USA, with more comparable initial treatment costs of $138,393 for amputation and $154,674 for operations other than amputation. 25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Another study from 2016 considered recurrent STS in the USA, with more comparable initial treatment costs of $138,393 for amputation and $154,674 for operations other than amputation. 25…”
Section: Discussionmentioning
confidence: 99%
“…16 Higher grade tumours, elevated patient BMI and diabetes were also associated with greater costs. 16,25 The association between tumour site and cost was unclear. Alamanda and Nelson et al observed higher costs for lower extremity lesions, however another study by Naghavi et al found that upper extremity tumours were more costly.…”
Section: Choice Of Endoprosthesismentioning
confidence: 99%
“…72 Surgery is the mainstay for the treatment in retroperitoneal sarcoma and one of the strongest predictors for local control is obtaining a complete resection with clear margins (R0). 73 The addition of preoperative radiation has been associated with higher rates of R0 resection 74 and an improvement in the locoregional control in retrospective series. 75 Therefore, practice has moved toward dose-painting, increasing radiation dose to areas where obtaining clear resection margins is challenging (eg, abutting neurovascular structures, perivertebral, paravertebral, and so on), in hopes of improving tumor response and thereby facilitating an R0 resection.…”
Section: Radiotherapymentioning
confidence: 99%
“…80 Current guidelines describe its use in the postoperative and intraoperative setting, using either an interstitial or an intracavitary approach. 74,75,77 The paradigm for recurrent or previously irradiated disease differs significantly from primary treatment and requires a more focal and personalized approach due to intrinsic treatment-resistant properties of recurrent disease and markedly increased likelihood for toxicity. Since brachytherapy delivers radiation from within, the areas receiving the highest radiation dose are the highest risk for microscopic disease (eg, tumor bed), with a rapid dose drop off to the neighboring normal tissue, which is ideal for previously irradiated sarcoma.…”
Section: Radiotherapymentioning
confidence: 99%
“…Accurate cancer detection and target therapy is essential for human health, as cancer is one of the most deadly diseases in the world today. As an effective chemotherapeutic agent, doxorubicin is often used to treat various tumor diseases, such as soft tissue sarcoma, 1 breast cancer, 2 malignant lymphomas, 3 and so forth. However, some side effects are found during and after doxorubicin treatment, such as the injury to the nontargeted tissues and irreversible cardiotoxicity.…”
Section: ■ Introductionmentioning
confidence: 99%